THE CHANGING LOOK AGNS MONITORING PROJECT - Oknyanskij, V. L.; Huseynov, N. A.; Lipunov, V. M.; Tatarnikov, A. M.; Shatsky, N. I.; Tsygankov, S. S.; Metlov, V. G.; Salmanov, I. R.; Gaskell, C. M. (Одеські астрономічні публікації, 2016)
The Changing Look AGNs (CL AGNs) are objects which undergo dramatic variability of the emission line profiles and classification type of which can move from one spectral class to another within very short time interval (from days to years). We start the project of spectral and photometric multiwavelength (from IR to X-ray) monitoring which include the selected set of AGNs also known as the CL AGNs. We are going to use 2-m Zeiss telescope (ShAO) for optical spectral observations, 2.5-m telescope of SAI for IR JHK photometry and spectrophotometery, small telescopes Zeiss-600, AZT-5 for BVRI photometry. We are also going to search for the new CL AGNs using the MASTER data. Furthermore, we can get historical light curves for the known and the new discovered objects using the MASTER opportunities. We are planning to apply for X-ray and UV observations of some CL AGNs with the SWIFT. We present some results of such monitoring of the transient object NGC2617. The main goal of the project is to investigate the possibilities for the repeating cases of the strong changes of spectral type at the CL AGNs. Investigation of such type of objects can be very informative for understanding the nature of these fast variations as well as physics of the AGNs.